People to Pixels - Siti Nur Faisha Binti Shaharudin (Nanyang Technological University, 2023)
‘Pixels to People’ explores the pervasiveness of surveillance and technology and its impacts. With the ongoing pandemic, the internet has become a space where people are able to turn to for comfort and refuge. Technology is undeniably a huge aspect of our lives, however, there are causes for concerns with the rising threats of surveillance and invasion of privacy. My work aims to highlight the dangers of technology; a realm where we are all being monitored without awareness, understanding or consent.